Readiness and motivation in digital civic engagement among tertiary students - Abril, Mary Ann C.; Manzanal, Johnrey N.; Dimaano, Glenda M.; Aguirre, Francisco V.; Babol, Melvin V. (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study addresses the challenge of enhancing civic engagement in higher education institutions by examining the predictive relationships between readiness, motivations, and digital civic engagement of tertiary students. Employing the quantitative, correlational research approach, data collected through survey questionnaires were analyzed using Minitab statistical software. Significant insights came from the 2,205 tertiary students selected through multistage random sampling, following strictly ethical standards to ensure data privacy and anonymity. As found, a moderate level of readiness underscores the need for targeted interventions, particularly to improve the civic behavior of students. Understanding and values motives emerged as dominant drivers of engagement, indicating the strong desire of students for personal growth and learning. While respondents occasionally exhibit digital engagement, it leans toward civic activities over political involvement, focusing primarily on information consumption rather than active collaboration. Emerging as a significant predictor of engagement, developing tailored initiatives to enhance readiness is crucial to positively influencing civic participation. Higher education institutions may use these findings to develop digital interventions that serve as catalysts for long-term civic engagement among students and engage in further research on other predictive factors.